2021
DOI: 10.3389/fenvs.2020.603668
|View full text |Cite
|
Sign up to set email alerts
|

Are Endophytic Bacteria an Option for Increasing Heavy Metal Tolerance of Plants? A Meta-Analysis of the Effect Size

Abstract: Plant endophytic bacteria have received special attention in recent decades for their ability to improve plant response to multiple stresses. A positive effect of endophytes on plant’s ability to cope with drought, salinity, nitrogen deficiency, and pathogens have already been demonstrated in numerous studies, and recently this evidence was consolidated in a meta-analysis of published data. Endophytic bacteria have also been implicated in increasing resistance to heavy metals in plants; despite the important b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 39 publications
(54 reference statements)
0
21
0
1
Order By: Relevance
“…This section shed light on how the interaction between the legumes and their associated endophytes can contribute in addressing the major types of abiotic stress face the plants which include drought, salinity, acidity/alkalinity and heavy metal toxicity [40].…”
Section: Soil Stress Mitigationmentioning
confidence: 99%
See 2 more Smart Citations
“…This section shed light on how the interaction between the legumes and their associated endophytes can contribute in addressing the major types of abiotic stress face the plants which include drought, salinity, acidity/alkalinity and heavy metal toxicity [40].…”
Section: Soil Stress Mitigationmentioning
confidence: 99%
“…Soil contamination with heavy metals results in toxic effects on plants [10]. To address this environmental problem, using association of plants with various microorganisms represents a sustainable strategy [40]. However, till now very few studies evaluated the effect of bacterial consortia for heavy metal contamination mitigation [40].…”
Section: Heavy Metal Contaminationmentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive release of heavy metals into the environment results in plants to develop different mechanisms to cope with their negative effects (Franco-Franklin et al, 2021). A study of plant responses and tolerance revealed that several genes are induced under heavy metal stress.…”
Section: Introductionmentioning
confidence: 99%
“…Endophytic bacteria can promote plant growth by several mechanisms that include indole acetic acid (IAA) synthesis, phosphate solubilization activity, production of siderophore under Fe-limiting conditions, improving mineral nutrient uptake by plants, and nitrogen fixation activity (Ryan et al, 2008). Endophytic bacteria can promote the growth of the plant hosts, even under abiotic stress conditions (Franco-Franklin et al, 2021). Several reports also indicate the induction of genes in plants that are central to heavy metal stress signaling in the presence of beneficial bacteria, such as Pseudomonas and Bacillus (Tiwari and Lata, 2018).…”
Section: Introductionmentioning
confidence: 99%